Clonal haematopoiesis in telomere biology disorders influences risk of haematological malignancy and overall survival - Groarke, Emma Maureen (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2024)
Telomere biology disorders (TBD) are a spectrum of diseases caused by germline variants in telomere repair and maintenance. They comprise one of the inherited bone marrow failure syndromes, a heterogenous group of disorders characterised by bone marrow failure, increased risk of haematological and solid malignancy, and other disease specific organ dysfunction. Our aims were to characterise myeloid malignancy in our cohort, perform somatic mutation testing in genes related to telomere maintenance and myeloid malignancy to elucidate the clonal landscape of TBD, and to see whether somatic mutations had clinical implications for TBD patients. We assessed a large cohort of TBD patients (n=208) from 3 institutions and found there was a cumulative incidence of 16% by age 16; however, this was significantly impacted by the patients' specific germline variant with TERC and DKC1 patients having the highest risk of MDS/AML, and TINF2 and biallelic RTEL1 patients having very low risk. When we sequenced patient samples, we found the clonal landscape was dominated by 4 somatic mutations, 2 in telomere related genes (POT1 and TERTp) and 2 related to myeloid malignancy (U2AF1 and PPM1D). We grouped mutations into: typical MDS/AML mutations (with a subgroup for splicing factors given their predominance and TP53), typical CH mutations, PPM1D, POT1 and TERTp. We used logistic regression and Kaplan Meier curves and found that MDS/AML associated mutations (including splicing factors) predicted both for MDS/AML and worse overall survival. TERTp mutations also predicted for worse OS but not myeloid malignancy. TP53 also strongly predicted for worse OS and the development of solid but not haematological malignancy. PPM1D and POT appeared to have an overall neutral effect on survival and did not positively influence blood counts. Using single cell analysis, we saw that U2AF1 acts as a founder clone for the development of subsequent malignant subclones. Our description of the clonal landscape of TBD help to drive our understanding of these disorders; we believe these somatic mutations arise as a compensatory mechanism to improve cell fitness. Splicing factor mutations and TP53 were identified as important biomarkers for cancer. Work is ongoing to better elucidate the functional consequences of these somatic mutations in TBD.
APPROVED